2000
DOI: 10.1021/la991071i
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Morphology in the Presence of Salts and Organic Additives

Abstract: Viscometry under Newtonian flow conditions has been used to study morphological changes in 0.3 M sodium dodecyl sulfate (SDS) micellar solutions in the presence of aliphatic amines (n-heptyl, C7NH2, or n-octyl, C8NH2) and different inorganic (MCl, M = Li, Na, K, or Rb; and NaX, X = Cl, Br, or SCN), organic salts (NaY, Y = salicylate (Sal), benzoate (Ben), anthranilate (An), or tosylate (Tos)), symmetrical quaternary bromides (R4NBr, R = H, CH3, C2H5, n-C3H7, n-C4H9, or n-C5H11) or tetrabutylphosphonium bromide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…They observed that an ionic surfactant increases the CP of TX-100 and the addition of an electrolyte diminishes the increase in CP. Kabir-ud-din et al [17,18] conducted a systematic study of micellar association due to the simultaneous presence of salts and organic additives and reported the combined effect of salts and organic additives on the micellar growth. In the present work, an effort was made to understand the interaction between solvent and additives leading to change in solubility and CP of TX-100.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that an ionic surfactant increases the CP of TX-100 and the addition of an electrolyte diminishes the increase in CP. Kabir-ud-din et al [17,18] conducted a systematic study of micellar association due to the simultaneous presence of salts and organic additives and reported the combined effect of salts and organic additives on the micellar growth. In the present work, an effort was made to understand the interaction between solvent and additives leading to change in solubility and CP of TX-100.…”
Section: Introductionmentioning
confidence: 99%
“…SDS, sodium bromide (NaBr), and tetra-n-butylammonium bromide (Bu 4 NBr) were the same as used earlier (29). All other chemicals, namely, urea, thiourea, n-propanol (PrOH), n-butanol (BuOH), and n-pentanol (PeOH), were of the best analytical grade available.…”
Section: Methodsmentioning
confidence: 99%
“…These observations are in good agreement with the data obtained as a function of SDS and added NaCl concentration. The aggregation behavior of SDS in aqueous solution in the presence of various organic additives is well documented [24][25][26]. The solubilization of alcohols in SDS micelles and subsequent effect to micellization and morphological features is investigated by different analytical methods [27][28][29][30].…”
Section: Influence Of Dodecyl Alcohol (C12oh) On Concentration Of Submentioning
confidence: 99%